Photovoice, claiming visibility, and women's farming identities in Australia. (November 2021) - Baker, Tagen Towsley; Radel, Claudia; Dale-Hallett, Liza; Forge, Catherine
Abstract: Despite an abundance of research on and growing social recognition of women's contributions to farming around the world, in many countries women farmers and their experiences are still relatively invisible to society. Museums Victoria's Invisible Farmer Project, the largest ever study of Australian women on the land, attempted to give voice to women farmers largely through a curated Facebook page. Our research, carried out between 2016 and 2018, examined the posted photographs and text as photovoice, supplemented by qualitative interviews, to understand the farming identities of participating women. Our analysis shows how these photovoices can represent a claim to visibility as farmers and can illuminate how women experience their own farming identities in relation to the landscapes of their farms and their perspectives on farmwork. We highlight the importance of emotional connections and carework in the women's identities. This study contributes to scholarship on emotional geographies by emphasizing the centrality of emotion in how women participating with the Invisible Farming Project construct and experience their farming identities. The importance of this finding lies in how greater visibility of women's farming identities might re-frame social understanding of farming as a relational and not just productive endeavor. Highlights: The Invisible Farmer Project attempted to give voice to women identifying as farmers. Women farmers continue to want more visibility despite some gains in recognition. Photovoice can help women farmers claim visibility and identity as farmers. Women farmers in this study experienced farming as emotional carework. Their photovoices illuminate an experience of farming as embedded and relational.